Primary brain tumours in adults. Issue 10145 (4th August 2018) - Lapointe, Sarah; Perry, Arie; Butowski, Nicholas A
Summary: Primary CNS tumours refer to a heterogeneous group of tumours arising from cells within the CNS, and can be benign or malignant. Malignant primary brain tumours remain among the most difficult cancers to treat, with a 5 year overall survival no greater than 35%. The most common malignant primary brain tumours in adults are gliomas. Recent advances in molecular biology have improved understanding of glioma pathogenesis, and several clinically significant genetic alterations have been described. A number of these ( IDH, 1p/19q codeletion, H3 Lys27Met, and RELA -fusion) are now combined with histology in the revised 2016 WHO classification of CNS tumours. It is likely that understanding such molecular alterations will contribute to the diagnosis, grading, and treatment of brain tumours. This progress in genomics, along with significant advances in cancer and CNS immunology, has defined a new era in neuro-oncology and holds promise for diagntic and therapeutic improvement. The challenge at present is to translate these advances into effective treatments. Current efforts are focused on developing molecular targeted therapies, immunotherapies, gene therapies, and novel drug-delivery technologies. Results with single-agent therapies have been disappointing so far, and combination therapies seem to be required to achieve a broad and durable antitumour response. Biomarker-targeted clinical trials could improve efficiencies of therapeutic development.